An improved line list for water vapor in the 1.5 µm transparency window by highly sensitive CRDS between 5852 and 6607 cm-1; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 130 - Leshchishina O.; Mikhailenko S. N. Semen Nikolaevich; Mondelain D.; Kassi S.; Campargue A. (2013, 2013)
Title screen